2005
DOI: 10.4103/0019-5545.55937
|View full text |Cite
|
Sign up to set email alerts
|

Stress and anxiety in parents of mentally retarded children

Abstract: Background:Studies comparing the stress perceived by parents of mentally retarded and normal children are limited.Aim:(i) To find whether there exists a difference in the perceived stress between both the parents of mentally retarded children, (ii) to study whether these stresses occur more frequently in parents of mentally retarded children compared with those of normal children, and (iii) to find any correlation between the severity of perceived stressors and the anxiety state of these parents.Methods:This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 9 publications
2
37
0
Order By: Relevance
“…The pattern of high burden among caregivers of children with disability has been noted both in the West (Mastrian et al 1996;Kurnat & Moore 1999;Dyson 2003;Kenny & McGilloway 2007) and in India (Edwardraj et al 2010;Divan et al 2012;Shyam et al 2014;Suresh et al 2014). Prior research also shows that caregivers of children with disabilities experience higher stress, anxiety and emotional strain (Dyson 1996;Majumdar et al 2005;Antshel & Joseph 2006;Kenny & McGilloway 2007;Karande et al 2009;Phetrasuwan & Miles 2009;Yang et al 2016), compared with parents of children without disabilities (Baker & McCal 1995). It is of significance to investigate caregiver psychological well-being, as poor well-being could lead to delayed diagnosis and discontinuation of treatment of a child with a disability (Weiss et al 2006).…”
Section: Stigma Of Disabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…The pattern of high burden among caregivers of children with disability has been noted both in the West (Mastrian et al 1996;Kurnat & Moore 1999;Dyson 2003;Kenny & McGilloway 2007) and in India (Edwardraj et al 2010;Divan et al 2012;Shyam et al 2014;Suresh et al 2014). Prior research also shows that caregivers of children with disabilities experience higher stress, anxiety and emotional strain (Dyson 1996;Majumdar et al 2005;Antshel & Joseph 2006;Kenny & McGilloway 2007;Karande et al 2009;Phetrasuwan & Miles 2009;Yang et al 2016), compared with parents of children without disabilities (Baker & McCal 1995). It is of significance to investigate caregiver psychological well-being, as poor well-being could lead to delayed diagnosis and discontinuation of treatment of a child with a disability (Weiss et al 2006).…”
Section: Stigma Of Disabilitymentioning
confidence: 97%
“…Prior research also shows that caregivers of children with disabilities experience higher stress, anxiety and emotional strain (Dyson ; Majumdar et al . ; Antshel & Joseph ; Kenny & McGilloway ; Karande et al . ; Phetrasuwan & Miles ; Yang et al .…”
Section: Introductionmentioning
confidence: 99%
“…After accepting that a child has an intellectual disability, the initial focus of a caregiver's physical and emotional energy would usually centre around training and skill development, combined with a positive hope of improvement (Majumdar, Da Silva, & Fernandes, 2005). After accepting that a child has an intellectual disability, the initial focus of a caregiver's physical and emotional energy would usually centre around training and skill development, combined with a positive hope of improvement (Majumdar, Da Silva, & Fernandes, 2005).…”
Section: Coping Styles and Psychological Statusmentioning
confidence: 99%
“…After accepting that a child has an intellectual disability, the initial focus of a caregiver's physical and emotional energy would usually centre around training and skill development, combined with a positive hope of improvement (Majumdar, Da Silva, & Fernandes, 2005). As the child increases in age, the gradual pace of improvement can also induce a sense of monotony and helplessness regarding the child's condition and subjective feelings of social isolation and life dissatisfaction set in (Majumdar et al, 2005). This could even be to an extent where caregivers often neglected their own chronic medical conditions and poor psychological well-being in favour of the child with disability and the family as a whole (Murphy et al, 2006).…”
Section: Coping Styles and Psychological Statusmentioning
confidence: 99%
“…Given this fact, it is not surprising that overwhelming majority of individuals with IDD live with their families and they have been a great source of support for persons with IDD. There has never been large-scale This innovative Act provides for establishment of National Trust for the welfare of persons with ID and their families, focus on empowerment of individuals with ID and their families through a number of services such as caregiver training programs, health insurance, training centres, greater participation of parent associations and NGO's working in the area in the care process, provision to establish respite and residential care facilities funded by the trust and run by parent associations, issue of guardianship for adults with ID, and for establishing service facilities to promote development of self-help groups of persons with disability to pursue the realization of their rights [ 15 ]. Studies also have reported poor awareness of government legislations and policies about disability benefi ts among families of persons with IDD [ 16 ].…”
Section: Familiesmentioning
confidence: 99%